Electrochemical Reduction of CO2 at Metal Electrodes in a Distillable Ionic Liquid. Issue 11 (10th May 2016) - Chen, Lu; Guo, Si‐Xuan; Li, Fengwang; Bentley, Cameron; Horne, Mike; Bond, Alan M.; Zhang, Jie
Abstract: The electroreduction of CO2 in the distillable ionic liquid dimethylammonium dimethylcarbamate (dimcarb) has been investigated with 17 metal electrodes. Analysis of the electrolysis products reveals that aluminum, bismuth, lead, copper, nickel, palladium, platinum, iron, molybdenum, titanium and zirconium electroreduce the available protons in dimcarb to hydrogen rather than reducing CO2 . Conversely, indium, tin, zinc, silver and gold are able to catalyze the reduction of CO2 to predominantly carbon monoxide (CO) and to a lesser extent, formate ([HCOO] − ). In all cases, the applied potential was found to have a minimal influence on the distribution of the reduction products. Overall, indium was found to be the best electrocatalyst for CO2 reduction in dimcarb, with faradaic efficiencies of approximately 45 % and 40 % for the generation of CO and [HCOO] −, respectively, at a potential of −1.34 V versus Cc +/0 (Cc + =cobaltocenium) employing a dimethylamine to CO2 ratio of less than 1.8:1. Abstract : By any metal necessary : Electrochemical reduction of CO2 in dimcarb was investigated with 17 types of metal electrodes. Although most of the transition and post‐transition metals produced H2 as the sole product, In, Sn, Zn, Au, and Ag were found to electrocatalyze the reduction of CO2 . Overall, In was found to be the best electrocatalyst for CO2 reduction in dimcarb, with faradaic efficiencies of approximately 45% and 40% for the generation of CO and [HCOO] −, respectively.